Exposure to low concentration of trifluoromethanesulfonic acid induces the disorders of liver lipid metabolism and gut microbiota in mice. (November 2020) - Zhou, Jiafeng; Shu, Ruonan; Yu, Chunan; Xiong, Ze; Xiao, Qingfeng; Li, Zezhi; Xie, Xiaoxian; Fu, Zhengwei
Abstract: Trifluoromethanesulfonic acid (TFMS) is the shortest chain perfluorinated compound. Recently, it has been identified as a persistent and mobile organic chemical with a maximum concentration of 1 μg/L in the environment. However, its toxicological mechanism remains unclear. In this study, to evaluate the liver and intestinal toxicity of TFMS in mammals, male mice were orally exposed to 0, 1, 10 and 100 μg/kg for 12 weeks. Our results showed that TFMS exposure reduced the epididymal fat weight in mice, caused the decrease of serum and liver triglyceride (TG) level and the increase of serum low density lipoprotein (LDL) level. Also, we observed the inflammatory cell infiltration in the liver of mice exposed to 10 μg/kg and 100 μg/kg TFMS, which was coupled with the increased mRNA expression levels of inflammatory factors such as COX2, TNF-α, IL-1β in the liver. In addition, the mRNA expression levels of lipid metabolism-related genes ( PPAR-α, ACOX, SCD1, PPAR-γ, etc.) were significantly decreased in the liver of mice after exposure to both doses of TFMS. We also found TFMS exposure caused the imbalance of cecal gut microbiota and change of cecal microbiota diversity. KEGG pathway predictions showed that the exposure of 100 μg/kg TFMS changed the synthesis and degradation of ketone bodies, benzoate degradation and several other metabolic pathways. Our findings indicated that TFMS exposure disturbed the liver lipid metabolism possibly via altering the gut microbiota. Highlights: Low concentration of TFMS induced lipid-related physiological change. TFMS exposure disturbed the hepatic lipid metabolism in mice. TFMS exposure caused the disorders of cecal gut microbiota.